A comparative study of femoral artery and combined femoral and axillary artery cannulation in veno-arterial extracorporeal membrane oxygenation patients - Jin, Na; Pang, Xin; Song, Shiyang; Zheng, Jin; Liu, Zhimeng; Gu, Tianxiang; Yu, Yang (Frontiers in Cardiovascular Medicine, 2024)
Objective: Veno-arterial extracorporeal membrane oxygenation (VA-ECMO) is a critical support technique for cardiac surgery patients. This study compares the outcomes of femoral artery cannulation versus combined femoral and axillary artery cannulation in post-cardiotomy VA-ECMO patients. This study aimed to compare the clinical outcomes of critically ill patients post-cardiac surgery under VA-ECMO support using different cannulation strategies. Specifically, the focus was on the impact of femoral artery (FA) cannulation versus combined femoral artery and axillary artery (FA+AA) cannulation on patient outcomes.Methods: Through a retrospective analysis, we compared 51 adult patients who underwent cardiac surgery and received VA-ECMO support based on the cannulation strategy employed-FA cannulation in 27 cases versus FA+AA cannulation in 24 cases.The FA+AA group showed significant advantages over the FA group in terms of the incidence of chronic renal failure (CRF) (37.50% vs. 14.81%, p=0.045), preoperative blood filtration requirement (37.50% vs. 11.11%, p=0.016), decreased platelet count (82.67±44.95 vs. 147.33±108.79, p=0.014), and elevated creatinine (Cr) levels (151.80±60.73 vs. 110.26±57.99, p=0.041), although the two groups had similar 30-day mortality rates (FA group 40.74%, FA+AA group 33.33%). These findings underscore that a combined approach may offer more effective hemodynamic support and better clinical outcomes when selecting an ECMO cannulation strategy.Despite the FA+AA group patients presenting with more preoperative risk factors, this group has exhibited lower rates of complications and faster recovery during ECMO treatment.While there has been no significant difference in 30-day mortality rates between the two cannulation strategies, the FA+AA approach may be more effective in reducing complications and improving limb ischemia. These findings highlight the importance of individualized treatment strategies and meticulous monitoring in managing post-cardiac surgery ECMO patients.